2000
DOI: 10.1002/1531-8249(200003)47:3<322::aid-ana7>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Sensory tricks in cervical dystonia: Perceptual dysbalance of parietal cortex modulates frontal motor programming

Abstract: Cervical dystonia is a disabling basal ganglia disorder characterized by an involuntary head deviation to one side. A typical but also mysterious feature is the impressive improvement of muscle spasms and involuntary head posture by application of a sensory facial stimulus (sensory trick). Here, we report the effect of a sensory trick on cortical activation patterns in 7 patients with cervical dystonia by using H215O positron emission tomography. The application of the sensory trick stimulus, resulting in a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(72 citation statements)
references
References 37 publications
3
67
0
2
Order By: Relevance
“…This suggests that this region is part of the network responding to the application of a trick manoeuvre (Naumann et al, 2000). The visual cortex proved to be involved in non-visual tasks in the past, such as tactile object recognition and tactile orientation, Braille reading in the congenitally blind and visual imagery.…”
Section: Dopamine Receptor Availabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…This suggests that this region is part of the network responding to the application of a trick manoeuvre (Naumann et al, 2000). The visual cortex proved to be involved in non-visual tasks in the past, such as tactile object recognition and tactile orientation, Braille reading in the congenitally blind and visual imagery.…”
Section: Dopamine Receptor Availabilitymentioning
confidence: 97%
“…In addition, the sensory trick leads to an increased activation of the parietal cortex ipsilateral to the direction of dystonic head rotation and bilateral occipital cortex. (Naumann et al, 2000) A study of patients with facial dystonia (blepharospasm and oromandibular dystonia) showed a significantly reduced primary sensorimotor area (PSA) blood flow response to vibration of the lower face in patients with facial dystonia compared to healthy controls. The peak activations the authors observed in this study were centered in the precentral gyrus, adjacent to the central sulcus, consistent with the primary motor cortex (Feiwell et al, 1999).…”
Section: Regional Cerebral Blood Flowmentioning
confidence: 99%
“…A recent PET study showed that the activities of the anterior SMA, the premotor cortex and even the primary SMC contralateral to the dystonic head rotation were decreased during sensory trick maneuvers. In addition, the bilateral visual cortex and part of the parietal cortex (especially, the posterior lobule) were activated even though no visual stimulation occurred during the sensory trick maneuvers [11]. Connections between the occipital and parietal cortexes that integrate visual and somatosensory information, are reflected by the increased activation in these two regions [12,13].…”
Section: Discussionmentioning
confidence: 97%
“…Connections between the occipital and parietal cortexes that integrate visual and somatosensory information, are reflected by the increased activation in these two regions [12,13]. It was suggested that these occipital and parietal regions are the part of the network that responds to sensory tricks in dystonia patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…They found an increase in contralateral parietal cortex activation during a trick manoeuvre. [6] Bara-Jimenez and coworkers examined the somatosensory cortical representation of the fingers in six patients with focal hand dystonia and found an abnormal homuncular representation of the hand area. [7] Another peculiarity in this case is that the lesion that caused the attacks was situated in the cortex and subcortical white matter.…”
mentioning
confidence: 99%